Biomimetic cobalt single atomic sites in carbon nitride nanosheets for photocatalytic reductive dechlorination of diclofenac - Junyan Pan; Luyao Sun; Rui Yan; Binhong Qu; Yang Qu; Liqiang Jing (Water Research, 2026)

Short-term biochar amendment enhances the chemical stability of soil organic carbon in the labile pools but may inhibit native SOC transformation into stable pool - Jinsuo Li; Zhaofeng Chang; Genghao Zhang; Luping Tian; Qu Wenhao; Peng Zhang; Kai Liu; Weiying Hou; Bo Pan (Soil and Tillage Research, 2026)

Therapeutic effects of 1,25-dihydroxyvitamin D3 with astragalus polysaccharide on insulin resistance in gestational diabetes mellitus rat models - Shuqi Yan; Haoyan Ma; Wenjian Li; Jiayuan Qu; Ming Wei; Chong Tan; Qizheng Pan; Shuping Ren; Yuhong Wang (Molecular Biology Reports, 2026)

Farrerol improves the maturation quality of porcine oocytes derived from small follicles associated with RAD51-related DNA repair responses - Lin Qi; Yingting Pan; Chaoqun Qu; Shuangyan Mo; Cuiting Peng; Hao Xie; Yulan Zhao; Yijie Tang; Wei Shen; Zhilong Chen; Zhonglin Tang (Theriogenology, 2026)

Water Management Controls Thiacloprid Degradation in Soil via Iron Redox Cycling with Biochar-Supported Zero-Valent Iron - Lin Pan; Shuai Qu; Longfei Liu; Wan Yang; Muhammad Mahroz Hussain; Shengsen Wang (Water, Air, & Soil Pollution, 2026)

Differential regulation of persulfate activation by biochar derived from co-pyrolysis of microplastics and sludge: From physicochemical properties to catalytic mechanisms - Zichao Qu; Baowei Zhao; Wenxiong Wu; Qi Guo; Ke Yang; Jianglong Pan (Journal of Water Process Engineering, 2026)

Isotope-informed assessment of groundwater nitrate attenuation and N2O-related risk in contrasting river-network lowlands - Shenhao Qu; Dongli She; Weilian Chen; Junhan Zhao; Li Zhang; Peng Chen; Yongchun Pan; Yongqiu Xia (Journal of Hydrology, 2026)

Iron-regulated crystallization in sensible-heat-driven glass-ceramics from molten lead-zinc smelting slag: Process-structure-property coupling and LCA quantification - Yibo Yang; Yusheng Tang; Hanguang Fu; Mengchen Xiao; Meichen Pan; Jixian Wu; Zhichuan Li; Zhe Tan; Zhixue Qu; Dean Pan; Xiaoguang Zhang (Process Safety and Environmental Protection, 2026)

Study on propeller ingestion noise in the wake of the SUBOFF bare hull model - Kaixing Ji; Denghui Qin; Qiaogao Huang; Nansha Gao; Yilin Qu; Guang Pan; Baowei Song (Ocean Engineering, 2026)

Apatite fingerprints the magmatic-hydrothermal processes of the Wajilitag alkaline‑carbonatite complex, NW China - Li-Peng Qin; Wu-Bin Yang; Guo-Feng Xu; Pan Qu; He-Cai Niu (Lithos, 2026)

In-situ elemental and boron isotopic compositions of tourmaline from the two-mica monzogranite in Ke'eryin rare metal orefield, Western China: Insights for granitic magma evolution - Deshui Yu; Zhaoxia Zhao; Pan Qu; Deru Xu; Shoujing Wang; Chi Ma; Fushuai Wei; Haibo Yan (Geochemistry, 2026)

Thermodynamic rebalancing of dissociation-coordination effect in weakly solvating electrolytes for high-performance sodium-ion batteries - Yan Meng; Yuanheng Wang; Qingjiang Liu; Hongji Pan; Jinghao Zhao; Xinhao Qu; Jia-Yan Liang; Xin Li (Chemical Engineering Journal, 2026)

Plant-soil-microbe interactions regulate plant- and microbial-derived carbon accumulation along a spatial vegetation gradient in arid salt marsh - Yaqing Pan; Peng Kang; Yilin Yang; Qing Wang; Chanyu Zhuang; Wenbin Qiao; Azmat Gyrat; Xuan Qu; Chao Guan (Applied Soil Ecology, 2026)

Corrigendum to “LUMIN: A novel algorithm for automated mixture quantification using 1D 1H NMR spectra” [Analytica Chimica Acta 1411 (2026) 345639] - Xinyuan Xie; Hongxu Zhang; Yingting Shi; Yuxia Jin; Kerui Fang; Qiuyi Chen; Jiayu Yang; Yuting Lu; Jianyang Pan; Haibin Qu (Analytica Chimica Acta, 2026)

Synergistic fermentation of Lactiplantibacillus plantarum 40 and 42 regulates browning in soybean paste and its mechanistic analysis - Huilin Ye; Qu Liu; Guoyang Pan; Jia Guo; LongKun Hu; Feiyu An; Ye Tian; Yaqi Wang; Junrui Wu; Rina Wu (Food Chemistry, 2026)

The game changer of biofilm in microplastic pollution and potential environmental risks: Unveiling the pivotal roles on surface modification, metal adsorption, and biological uptake - Yun Xiao; Haixia Pan; Meng Zhang; Xiaoyu Han; Hongqin Guo; Xiaochuan Qu; Yutian Shi; Songying Cao; Ning Zhang; Xin Zhao; Baoqin Liu (Environmental Research, 2026)

Model-driven structural seismic response reconstruction and parameter identification based on machine learning - Pan Liu; Jun Qiu; Zhongguo Guan; Jianzhong Li; Quincy Ma; Hongya Qu (Engineering Structures, 2026)

Synergistic ionic liquid dispersion and pre-stretching strategy for stable, electromechanical robust fiber sensors - Yuying Zhang; Yuteng Lei; Lehao Pan; Yuzhu Zhai; Jiahui Li; Linghui Kong; Mingwei Tian; Lijun Qu; Yijun Jiang (Chemical Engineering Journal, 2026)

Real-time in-situ H2O2 quantification in high-biomass marine environments with a robust NiCo-MOF nanosheet electrode - Dan Zhao; Yuankai Lu; Huixiu Mao; Mengjie Qu; Yiwen Pan; Hangzhou Wang (Analytica Chimica Acta, 2026)

LUMIN: A novel algorithm for automated mixture quantification using 1D 1H NMR spectra - Xinyuan Xie; Hongxu Zhang; Yingting Shi; Yuxia Jin; Kerui Fang; Qiuyi Chen; Jiayu Yang; Yuting Lu; Jianyang Pan; Haibin Qu (Analytica Chimica Acta, 2026)

A novel neurovascular coupling analysis method based on simultaneous EEG-fNIRS for investigating the effects of working memory load - Yu Wang; Qi Pan; Bin Wen; Qiong Wu; Qiumin Qu; Jilun Ye; Xu Zhang; Jin Xu (Medical & Biological Engineering & Computing, 2026)

Editorial Expression of Concern: Knockdown of NOB1 expression inhibits the malignant transformation of human prostate cancer cells - Xiangmin Zhang; Dongxu Zhang; Fajun Qu; Yi Hong; Jianwei Cao; Xiuwu Pan; Lin Li; Yi Huang; Hai Huang; Lei Yin; Lu Chen; Jizhong Ren; et al. (Molecular and Cellular Biochemistry, 2026)

From waste to resource: Fly ash regeneration salt recycling based on chlor-alkali production - Jun Li; Kexuan Yang; Shuping Pan; Hongxing Qu; Zhanheng Zhu; Jingsong Liu; Xiaodong Li (Journal of Hazardous Materials, 2026)

Pyrite-functionalized biochar via the mechanochemical ball-milling method enhanced soil lead/cadmium passivation and promoted plant growth - Shuqi Wei; Lei Wang; Wenqi Zhang; Zhengni Pan; Xinrui Song; Qi Liu; Yue Tao; Jianhua Qu; Ying Zhang (Journal of Hazardous Materials, 2026)

Selenium nanoparticles alleviate chromium stress in wheat (Triticum aestivum L.) by inhibiting root uptake, enhancing antioxidant capacity, and regulating the rhizosphere microbiome - Lili Qu; Hanchi Liu; Jia Li; Xin Li; Ran Chen; Xin Liang; Xuewei Jia; Pan Wu; Xiaohui Qiao; Chunping Xu (Journal of Environmental Management, 2026)

MSC-sEV Promote Regeneration of Cochlear Spiral Ganglion Neurons and Myelin Sheaths in 3D Culture System - Yunyou You; Anning Chen; Jiaxi Qu; Yiman Guo; Jing Pan; Taolue Yu; Fan Shu; Jie Tang; Hongzheng Zhang (Neuroscience Bulletin, 2026)

A critical review of biochar adsorption mechanisms and performance in soil remediation of perfluoroalkyl and polyfluoroalkyl substances - Xue Pan; Bo Yang; Fanhua Meng; Yufang Wei; Wenbing Tan; Kunlong Hui; Chengtun Qu; Chen Shen; Beidou Xi (ENGINEERING Environment, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Lycopene ameliorates swainsonine-induced autophagy in rat renal tubular epithelial cells via the endoplasmic reticulum stress UPR pathway - Pan Wang; Lihui Tang; Liwen Yang; Congcheng Zhang; Hai Yin; Siqi Hou; Yin Shao; Yingying Qu; Hao Lu (Research in Veterinary Science, 2026)

An interfacially engineered Ni2P/Fe2P heterostructure grown on NiFe PBA/NF as a high-efficiency bifunctional electrocatalyst for overall water splitting - Pan Qu; Zhenlu Zhao (Fuel, 2026)

Dietary lipid levels modulate enrofloxacin-induced antibiotic resistance and metabolic dysfunction in Pacific white shrimp (Litopenaeus vannamei): assessing the dietary risk and metabolic impact in edible tissues - Jiahao Song; Yucheng Liu; Yifei Pan; Kangyuan Qu; Bin Huang; Xianjie Chen; Yuxuan Ma; Youxi Li; Jiajie Chen; Shuyan Chi; Beiping Tan; Shiwei Xie (Food Chemistry, 2026)

Employing L-cysteine-mediated modulation for nickel biorecovery: Bioseparation-photocatalytic upcycling from wastewater - Shunling Li; Peng Cui; Zhaosheng Zhang; Fenxiang Li; Pan Bo; Qing Qu (Environmental Research, 2026)

High-efficiency solar-driven photothermal membrane distillation via permeate-side interfacial heating - Qian Yu; Mengfei Xie; Rong Chen; Kuiling Li; Liqiu Zhang; Bo Pan; XueJun Pan; Junhui Zhang; Dan Qu (Desalination, 2026)

Research on the Lightweight DAMS-Net and Transfer Learning Methods for Microseismic P-Wave Arrival Time Picking - Xiaozheng Xu; Hao Luo; Yishan Pan; Liang Wang; Junhao Qu; Li Zhang (Rock Mechanics and Rock Engineering, 2026)

Effect of flow conditions on solid-liquid two-phase flow characteristics in the multistage deep-sea mining pump - Leilei Ji; Jie Yang; Wei Li; Weidong Shi; Xinrui He; Yang Yang; Ling Zhou; Fei Tian; Bing Qu; Bo Pan; Ramesh K. Agarwal (Ocean Engineering, 2026)

Cryoprotective effects and mechanisms of heterologously expressed wheat-derived antifreeze peptide on probiotics - Xiaoge Liu; Jingjing Wang; Yingjing Qu; Long Pan; Xin Wang; Kangyi Zhang; Quan-Ping Liu; Na Liu; Jihong Huang; Ai-Mei Liao (Food Bioscience, 2026)

Molecular switch engineering manipulates Zn ion transfer enabling fast charging Zn-ion batteries - Yuying Li; Qing Xin; Pan Feng; Junnan Qu; Jingxuan Ren; Jiahao Lei; Jinhao Chen; Jingyao Li; Renming Liu; Xintao Long; Xinli Guo; Dan Luo; et al. (Chemical Engineering Journal, 2026)

Direct identification and susceptibility testing of positive blood cultures: a large-scale evaluation of an ammonium chloride-based in-house workflow - Xiaoli Zhang; Enhua Sun; Yixuan Qu; Yiwen Gao; Fuyao Hu; Weiwei Sun; Wei Li; Hongwei Pan (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Efficient glycolysis of PET waste with Zn-mediated ionic liquid catalyst: Uncovering the mechanism of dimolecular activation and kinetic acceleration - Xin Wang; Pan Liu; Hui Wang; Zhenyan Liu; Wenbin Qu; Jiayu Huang (Journal of Environmental Chemical Engineering, 2026)

Temperature-driven anaerobic membrane distillation bioreactor for simultaneous bioenergy recovery and wastewater reclamation: Performance trade-offs, fouling mechanism, and microbial community shifts - Haiyang Yang; Zhimeng Yang; Jiahui Liang; Huarong Yu; Fangshu Qu; Yuxuan Wan; Zhihui Pan; Dan Qu; Liu Yang (Chemical Engineering Journal, 2026)

Design and effectiveness evaluation of multistage check dams for debris flow of tailings dam failure - Meixian Qu; Zhan Yan; Hao Wu; Zhenkai Pan; Shaohua Hu (Natural Hazards, 2026)

Multi-spectroscopy reveals selective oxidation for ultrafiltration membrane fouling control in wastewater reuse - Qingshui Fan; Huarong Yu; Yuxuan Wan; Haiyang Yang; Zhihui Pan; Fangshu Qu (Water Research, 2026)

Development of naringenin-loaded foxtail millet prolamin nanoparticles modified with hyaluronic acid: Characterization, stability, and bioaccessibility - Wen Zhang; Wenjing Liang; Zhizhe Zhang; Jiaxi Wang; Lijun Pan; Ao Qu; Runyan Wang; Yuying Tang; Pei Zhao; Shuaishuai Gao; Zijian Wu (Food Chemistry, 2026)

Analysis of phenomics, metabolomics and transcriptomics reveals the differences in fruit quality between on-tree bagged and non-bagged apples - Yuan Zhao; Yinxin Tang; Ritao Qu; Jing Guo; Yufei Gu; Min Xiao; Chengwei Wu; Qi Pan; Manyu Zhang; Yuandi Zhu (Food Chemistry, 2026)

Driving factors and predictive model of dissolved N2O concentrations in a complex aquatic network - Li Zhang; Dongli She; Menghua Xiao; Yongchun Pan; Cheng Lu; Shenhao Qu; Taohong Cao; Yongqiu Xia (Environmental Research, 2026)

Challenges and Opportunities in Tunnel Wastewater Treatment: Engineering Perspectives for Sustainable Management - Debin Tian; Wenrong Ma; Liang Du; Hong Chen; Yang Zhou; Jun Tan; Pan Zhang; Yi Sun; Ben Xiao; Yansen Qu; Yali Chen; Xinghua Chang (Water, Air, & Soil Pollution, 2026)

A novel phage and its protective effects against Hafnia paralvei in Cyprinus carpio Koi - Lingting Pan; Chenxin Qu; Wencai Liu; Long Tan; Xiaoying Jing; Jinpeng Xu; Wei Lin; Dengfeng Li; Yigang Tong (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Integrated autotrophic iron-dependent denitrification and anammox for simultaneous nitrogen and phosphorus removal from low C/N ratio wastewater - Xiaofan Yang; Liqiu Zhang; Hang Zhang; Shugeng Li; Zhihui Pan; Peng Wang; Huarong Yu; Fangshu Qu (Journal of Water Process Engineering, 2026)

RSM-based development and optimization of a novel fracture sealing material for secondary grouting in extraction boreholes - Junxiang Zhang; Yijian Guo; Bo Li; Yadong Bian; Shumin Ding; Lina Qu; Zhenfeng Wang; Yaocai Tang; Pan Chen (Fuel, 2026)

Determination of fumonisins in grains and feed: an efficient clean-up method combined with lC-MS/mS - Xin Zhou; Qiang Hou; Bin Qu; Xinyu Guo; Xuesong Wang; Canping Pan; Baiqin Zheng; Aijun Li (Food Additives & Contaminants: Part A, 2026)

Dynamic Changes in Serum Biochemical Indices and Alternative Splicing Events Revealed Molecular Regulatory Mechanisms in Rainbow Trout Under Copper Stress - Junhao Lu; Jinqiang Quan; Jing Zhou; Yucai Pan; Jiahui Zhang; Ziguo Wang; Yuling Qu (Marine Biotechnology, 2026)

Spin valve effect in hybrid spin filters with Cr2Ge2Te6 - Xiaoyu Wang; Shuxi Wang; Ying Zhang; Yi Ding; Xueyan Dong; Lin Zou; Shaojie Liu; Miao He; Takashi Taniguchi; Kenji Watanabe; Xuan Pan; Lei Zhang; et al. (Science Bulletin, 2026)

Enhanced CO2 desorption from monoethanolamine solution using TiO(OH)2-modified diatomite catalyst - Pan Zhang; Zhongfa Zha; Jiawen Yang; Xinbo Wang; Jianwen Song; Shuming Du; Liwen Li; Kun Zhao; Dong Fu; Lemeng Wang; Jun Ke; Pengfei Qu (Process Safety and Environmental Protection, 2026)

Application of functional graphene composites in heavy metal ion monitoring: A review - Han Zheng; Guangfei Qu; Keheng Pan; Junyan Li; Yuchen Shi; Changfei Guo; Wanyuan Du (Journal of Water Process Engineering, 2026)

Nitrate dynamics in engineered plain polder–river networks driven by surface water–groundwater interactions - Shenhao Qu; Dongli She; Yongchun Pan; Menghua Xiao; Peng Chen; Junhan Zhao; Taohong Cao; Xinni Ju; Li Zhang; Cheng Lu; Yongqiu Xia (Journal of Hydrology, 2026)

Unveiling the black box: Multi-omics reveal how biochar supercharges synthetic biofilms for superior bioremediation - Bo Zhang; Xiaoying Hu; Lu Han; Zhen Guo; Yongqi Liu; Huiyao Li; Yuze He; Tianyu Liu; Qingyuan Pan; Yi Mu; Jianhua Qu; Hongqi Yu; et al. (Journal of Hazardous Materials, 2026)

Evolved Saccharomyces cerevisiae strains exhibit superior freeze-thaw tolerance and frozen dough performance via multi-level adaptations - Tianzhi Qu; Chenwei Pan; Jian Chen; Jianghua Li; Anqi Chen (Food Research International, 2026)

Corrigendum to “Composite inclusion complexes containing hyaluronic acid/chitosan nanosystems for dual responsive enrofloxacin release” [Carbohydrate Polymers 252 (2021) 117162] - Yuda Liu; Dongmei Chen; Aoxue Zhang; Man Xiao; Zhenxia Li; Wanhe Luo; Yuanhu Pan; Wei Qu; Shuyu Xie (Carbohydrate Polymers, 2026)

Heat Stress Induces Cognitive Impairment Through ACSL4-Mediated Lipid Peroxidation and Subsequent Ferroptosis - Qicheng Zhou; Xinyao Liu; Wenlan Pan; Yicui Qu; Wenjing Shi; Gen Miao; Lu Huang; Xin Li; Mengyu Cai; Hongxia Li; Hui Shen (Molecular Neurobiology, 2026)

Groundwater denitrification dynamics and N2O emissions across diverse cultivated land types in the Taihu lake region - Taohong Cao; Dongli She; Yongchun Pan; Jiamin Ge; Shenhao Qu; Xinni Ju; Xuan Huang; Yongqiu Xia; Daniel Fernàndez-Garcia (Water Research, 2025)

O-Hf-Mg isotopic signals of recycled oceanic crust in the Early Cretaceous I-type granites from NE China - Ao Li; Wu-Bin Yang; Xu Zhao; He-Cai Niu; Ning-Bo Li; Pan Qu (Lithos, 2025)

Elevated salinity limits nitrogen removal from ditch systems in arid inland regions - Alimu Abulaiti; Dongli She; Zhenqi Shi; Yongchun Pan; Junhan Zhao; Shenhao Qu; Yongqiu Xia (Journal of Hydrology, 2025)

Developing MLR, SVM and ANN QSAR models to predict the removal kinetics of phenolic pollutants in ferrate(VI) and silver oxide catalyzed ferrate(VI) oxidation systems - Shengnan Zhang; Bingru Tian; Xiaoxue Pan; Moustafa M.G. Fouda; Ruijuan Qu (Journal of Environmental Chemical Engineering, 2025)

Epidote U–Pb geochronology reveals staged skarn formation linked to geodynamic transformations in convergent continental margins - Shuang Yan; Wu-Bin Yang; Ning-Bo Li; Pan Qu; He-Cai Niu (Geochimica et Cosmochimica Acta, 2025)

Multifunctional sutures coated with metal-phenolic networks for dynamic antibacterial and antioxidant therapy - Qianchen Huang; Dongyu Yu; Siyu Li; Renhai Zhao; Guangqi Cheng; Zhenghai Qu; Bin Wang; Shuang Wang; Pan He; Ling Li; Jiwei Li (Chemical Engineering Journal, 2025)

Chemical constituents of Alchornea rugosa and their chemotaxonomic significance - Xin-Xin Liang; Ming-Hao Mao; Si-Cheng Jin; Jia-Yi Zhang; Lei Wu; Jiao-Ying Qu; Jiao-Jiao Pan; Xiang-Guo Meng (Biochemical Systematics and Ecology, 2025)

Link between Double-Diffusive Staircases and Water Masses in the Arctic Ocean - Xue-Long Song; Sheng-Qi Zhou; Ling Qu; Yuan-Zheng Lu; Lu-Dan Pan (Thalassas: An International Journal of Marine Sciences, 2025)

Visible light-mediated persulfate activation by magnetite: Wavelength-specific radical generation and bisphenol AF transformation pathways - Ying Zhang; Cheng Qin; Jiajia Pang; Xiaoxue Pan; Rehab Khaled Mahmoud; Xiaosheng Tang; Zunyao Wang; Ruijuan Qu (Science of The Total Environment, 2025)

Insights into the influence of anthropogenic forcing on sediment dynamics in the Yellow River basin - Chao Wu; Gangjian Wei; Fang Huang; Peng Qian; Pan Qu; Honghua Lu; Xiangmin Zheng; Zhengbin Deng (CATENA, 2025)

Population pharmacokinetics and pharmacodynamics of meropenem in critically ill patients with renal impairment or on continuous renal replacement therapy - Chen Feng; Jiangyujing Bian; Yuchen Qu; Yunli Yu; Yueyuan Wang; Xin Du; Yewen Sun; Guanjun Wang; Jiao Xu; Jianjun Zhu; Jie Pan (European Journal of Clinical Pharmacology, 2025)

Dynamic integrated optimization of batching and routing in narrow-aisle order picking systems with congestion consideration - Yanghua Pan; Shanshan Li; Ting Qu; Liqiang Ding; Naiqi Wu; George Q. Huang (Swarm and Evolutionary Computation, 2025)

An improved time-domain spectral matching algorithm for peak adjustment and convergence efficiency optimization - Pan Liu; Xinyan Jiang; Jianzhong Li; Hongya Qu (Soil Dynamics and Earthquake Engineering, 2025)

Integrated phosphorus removal and recovery using MgO2-magnetic biochar: A circular approach combining fenton chemistry and soil fertility enhancement - Zhibo Zhang; Chuchu Feng; Miaoqu Wang; Kuok Ho Daniel Tang; Ronghua Li; Guangzhou Qu; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

Virtual screening and molecular mechanism of novel anti-benign prostatic hyperplasia peptides from Syngnathus schlegeli - Ailing Duan; Xiangxi Yi; Xiangtan Zhao; Si Li; Xinjian Qu; Geng Qin; Qiang Lin; Hua Chen; Peng Wan; Deke Chen; Xin Chen; Weimao Zhong; et al. (Food Research International, 2025)

Exploring the functional diversity of wild Saccharomyces cerevisiae strains for breadmaking applications - Chenwei Pan; Jiaming Li; Tianzhi Qu; Hui Liu; Weiming Xiao; Bo Chen; Anqi Chen; Jian Chen (Food Bioscience, 2025)

Gradient multi-component interphase enabling highly reversible magnesium metal anode in fluorinated alkoxyborate-based electrolytes - Yuhang Chen; Yiming Zhang; Zhimeng Tang; Zhenyu Zhang; Le Tong; Xuemin Gan; Xing Shen; Guangsheng Huang; Qian Li; Baihua Qu; Fusheng Pan; Jingfeng Wang (Chemical Engineering Journal, 2025)

Improvement of isolation and drug testing methods for Corynebacterium spp. in clinical specimens of granulomatous mastitis - Fang Liu; Yewei Yuan; Ruiyang Wu; Ninghua Tang; Kehua Chen; Kui Fan; Wei Cheng; Qu Pan (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Genesis of the Debao Sn-Cu Deposit in South China: Insights from Pb-S-He-Ar Isotopes - Jian Zhang; Lichuan Zhang; Quan Ou; Pan Qu; Yinqiao Zou; Hongxia Yu (Journal of Earth Science, 2025)

Seismic performance of hybrid seismic isolation bearing system: shake table test and nonlinear numerical analysis - Pan Liu; Jianzhong Li; Jianfeng Gao; Xinyan Jiang; Hongya Qu (Soil Dynamics and Earthquake Engineering, 2025)

Promotion of grain growth via solvent fumigation for wide-bandgap perovskite solar cells with low VOC deficit and perovskite/TOPCon tandem solar cells with efficiency >30% - Xiang Liao; Yuanfang Zhang; Zijian Qu; Qiang Zeng; Mingjun Zhang; Jungan Wang; Yining Pan; Jie Yang; Damin Zheng; Zengsheng Liu; Linhong Li; Menglei Xu; et al. (Science Bulletin, 2025)

Efficient phosphate removal from wastewater using Mg/Fe-functionalized tea stalk biochar through green synthesis and bio-assembly method - Huiyao Li; Shuai Shi; lrina lvshina; Ziyan Wang; Jing Gui; Ruolai Wang; Chunyu Pan; Yiwen Ning; Jianhua Qu; Siyue Han; Ying Zhang (Process Safety and Environmental Protection, 2025)

Synergistic infrared Co-pyrolysis for integrated resource Recovery: Gas-Induced metal extraction from spent lithium-ion batteries and bio-oil upgrading - Moshan Li; Erfeng Hu; Zuohua Liu; Guangwen Xu; Jianglong Yu; Zhaohui Lu; Guocan Zheng; Dean Pan; Rui Qu (Journal of Cleaner Production, 2025)

Efficient catalysis removal of nitric oxide with microemulsion enhanced by corona discharge - Congqing Yang; Keheng Pan; Guangfei Qu; Junyan Li (Journal of Environmental Chemical Engineering, 2025)

Gel-based evaporators for solar desalination of high concentration brines - Zihui Wang; Xinjuan Liu; Yuquan Li; Bowen Wang; Zhongkai Qu; Min Xu; Likun Pan (Desalination, 2025)

Synergetic photocatalytic activation of persulfate by Ti3C2/g-C3N4 for sterilization and antibiotic degradation - Jie Mao; Hongmei Li; Haobo Pan; Chenchen Wang; Zhenao Gu; Yaohhui Bai; Jiuhui Qu (Chemical Engineering Journal, 2025)

The combination of FLI, ITS, pFF, and citrate improves the developmental potential of gilt oocytes during in vitro maturation - Zhilong Chen; Caiyong Zhang; Chao Yan; Cuiting Peng; Hao Xie; Yingting Pan; Lin Qi; Chaoqun Qu; Yulan Zhao; Zhonglin Tang (Animal Reproduction Science, 2025)

Straw mulch and orchard grass mediate soil microbial nutrient acquisition and microbial community composition in Ziziphus Jujuba orchard - Peng Kang; Yaqing Pan; Jinpeng Hu; Xuan Qu; Qiubo Ji; Chanyu Zhuang; Yufeng Ren; Jun Zhou; Tianjun Wei (Plant and Soil, 2025)

Enhancing Ready-to-Implementation subseasonal crop growth predictions in central Southwestern Asia: A machine learning-climate dynamical hybrid strategy - Tao Zhu; Mengqian Lu; Jing Yang; Qing Bao; Stacey New; Yuxian Pan; Ankang Qu; Xinyao Feng; Jun Jian; Shuai Hu; Baoxiang Pan (Agricultural and Forest Meteorology, 2025)

Identification and taste presentation characteristics of umami peptides from soybean paste based on peptidomics and virtual screening - Guoyang Pan; Feiyu An; Junrui Wu; Yaqi Wang; Li Deng; Xing Tong; Shuaiqi Ji; Jinhui Jiang; Qu Liu; Ning Yang; Dongbing Tao; Rina Wu (Food Chemistry, 2025)

Yellow mealworm (Tenebrio molitor) meal replacing dietary fishmeal alters the intestinal microbiota, anti-oxidation and immunity of large yellow croaker (Larimichthys crocea) - Peng Qu; Jing Yuan; Yang Wu; Shuangjie Tian; Zhenhua Wu; Peng Chen; Mingzhu Pan; Huasong Weng; Kangsen Mai; Wenbing Zhang (Fish & Shellfish Immunology, 2025)

Shaddock peels biochar doping with Fe-Co bimetal for peroxymonosulfate activation on the degradation of tetracycline: The influence of HCO3− and PO43− - Haochen Li; Jiahui Wu; Ao Ren; Yao Qu; Xiaofei Zong; Yaoyao Gong; Dandan Wang; Yuxuan Ye; Qiang Li; Zhenbin Wu; Fei Pan (Environmental Research, 2025)

HFNet: Semantic and Differential Heterogenous Fusion Network for Remote Sensing Image Change Detection - Yang Han; Jiayi Li; Yang Qu; Leiguang Wang; Xiaofeng Pan; Xin Huang (Journal of Geovisualization and Spatial Analysis, 2025)

Progestogen is a potential trigger initiating sex inversion in rice field eel (Monopterus albus) - Xiancheng Qu; Jiaoyun Jiang; Min Li; Jianhua Ye; Lisa Pan; Qinhua Zhang; Guofang Zhong; Xinchao Zhu; Yifang Du; Xianhui Li (Fish Physiology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Deciphering the operation efficiency and fermentation model in mixed microbial cultures system for poly(3-hydroxybutyrate-co-3-hydroxyvalerate) synthesis - Leizhen Zhao; Jiachen Pan; Tao Wan; Feng Huang; Shuai Zhao; Jia Zhou; Xiao Ma; Jianhang Qu; Xiao-Ming Ji (Journal of Environmental Management, 2025)

Environmental low-dose nanosized carbon black exposure aggravates lung fibrosis-induced by radiation in vivo and in vitro - Can Qu; Chenjun Bai; Jinhua Luo; Dafei Xie; Huiji Pan; Lihui Xuan; Jingjing Yang; Yongyi Wang; Hua Guan; Pingkun Zhou; Ruixue Huang (Science of The Total Environment, 2025)

Persimmon (Diospyros kaki thunb.) leaf polyphenols: Impact on digestive degradation and human gut microbiota regulation - Jing Liu; Jialin Qu; Ying Gao; Yuanyuan Gao; Yuexin Hao; Zhaofeng Pan; Xiaohua He; Bin Liu; Xuchang Duan (Food Bioscience, 2025)

Melatonin enhances salt tolerance by promoting CcCAD10-mediated lignin biosynthesis in pigeon pea - Feng Pan; Hongquan Li; Ming Qu; Xiaoli An; Jie Yang; Yujie Fu (Theoretical and Applied Genetics, 2025)

Assessment of high-position glacial valleys in Southeast Tibet, China: an integrated approach using remote sensing, UAV, field investigation, and numerical simulation - Congyan Ran; Shishu Zhang; Xinfu Xing; Haizhu Qu; Zhanglei Wu; Da Zheng; Zhenhui Pan; Maohong Yao; Kai Zhang (Natural Hazards, 2025)

Full-coupled post-fire performance analysis of geopolymeric recycled aggregate concrete-filled steel tubular columns - Kai Xiang; Xing-Yu Qu; Zhu Pan; Tian-Yi Song; Hongyuan Zhou; Qing-Hua Tan (Engineering Structures, 2025)

circTP63-N suppresses the proliferation and metastasis of nasopharyngeal carcinoma via engaging with HSP90AB1 to modulate the YAP1/Hippo signaling pathway - Dan Wang; Sicheng Zuo; Junshang Ge; Hongke Qu; Jie Wu; Na Yi; Lei Shi; Yumin Wang; Yongzhen Mo; Chunmei Fan; Yi He; Pan Chen; et al. (Science China Life Sciences, 2025)

Dual-bioaugmentation strategy to simultaneously mitigate biofouling and promote methanogenesis in AnMBR - Yimeng Li; Huarong Yu; Haiyang Yang; Yuxuan Wan; Zhihui Pan; Fangshu Qu (Water Research, 2025)

Enhancing the carbon sequestration potential of urban green space: A water–energy–carbon fluxes perspective - Yilun Qu; Yan Shi; Xu Wu; Minghui Zhu; Pengfei Zhu; Xiao Zhang; Shuangying Le; Yuan Ren; Jianyun Pan; Yixiang Wang (Urban Forestry & Urban Greening, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Supplementation of recombinant human lysozyme into diets affects the growth performance, muscle quality, immunity and intestinal microbiota in large yellow croaker Larimichthys crocea - Dayin Liu; Peng Qu; Yingxu Huangfu; Xinyu Wang; Mingzhu Pan; Yang Wu; Kangsen Mai; Wenbing Zhang (Fish & Shellfish Immunology, 2025)

Experimental analysis on post-fire performance of GRAC filled steel tubular columns and thermal properties of GRAC - Tian-Yi Song; Xing-Yu Qu; Zhu Pan; Hongyuan Zhou; Kai Xiang; Qing-Hua Tan (Engineering Structures, 2025)

Morphometric analysis of the female reproductive tract: influence of long-term inhalation of trace amounts of sevoflurane - Haili Wang; Haibo Qu; Ailing Yang; Daru Guo; Lili Quan; Zhaodong Liu; Xiaoli Shi; Xibo Zhao; Yuanbo Feng; Tao Liu; Hua Pan (Journal of Molecular Histology, 2025)

NIR-driven GOx-like nanozyme-modified injectable thermoresponsive hydrogel for antibacterial therapy and bone regeneration in periodontitis - Changxing Qu; Tianying Luo; Ruxia Han; Dong Mo; Kun Shi; Xicheng Li; Zhongwu Bei; Meng Pan; Songtao Tan; Jun Liu; Zhiyong Qian (Chemical Engineering Journal, 2025)

Trends in conductive MOFs for sensing: A review - Lingli Qu; Yiwen Xu; Weikang Cui; Lingjuan Wu; Yi Feng; Yangyang Gu; Hongzhi Pan (Analytica Chimica Acta, 2025)

Responses of various organic carbon pools to elevated temperatures in soils - Yafeng Han; Chenchen Qu; Xiping Hu; Pan Sun; Jie Kang; Peng Cai; Xingmin Rong; Wenli Chen; Qiaoyun Huang (Science of The Total Environment, 2024)

Degradation of 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV328) in soil by FeS activated persulfate: Kinetics, mechanism, and theoretical calculations - Xiaoyu Li; Yue Bu; Jianqiao Xu; Haifa E. Alfassam; Hassan A. Rudayni; Ahmed A. Allam; Xiaoxue Pan; Zunyao Wang; Ruijuan Qu (Environmental Pollution, 2024)

A novel mutation in hERG gene associated with azithromycin-induced acquired long QT syndrome - Yun-Jiu Cheng; Yang Wu; Hui-Qiang Wei; Yi-Jian Liao; Li-Ping Qu; Yue-Han Pan; Li-Juan Liu; Wen-Tao Bi (Molecular Biology Reports, 2024)

Engineered bispecific antibodies with enhanced breadth and potency against SARS-CoV-2 variants and SARS-related coronaviruses - Fangfang Chang; Qian Wu; Yabin Hu; Zhendong Pan; Yong-Chen Liu; Yue-Zhou Li; Mihnea Bostina; Wenpei Liu; Ping Zhao; Xiaowang Qu; Yi-Ping Li (Medical Microbiology and Immunology, 2024)

Gastrodin ameliorates diabetic nephropathy by activating the AMPK/Nrf2 pathway - Shuqin Zhao; Qingyun Pan; Xiaolin Lin; Xian Li; Li Qu (Journal of Molecular Histology, 2024)

Research progress in mechanisms and properties of nano-modified interface transition zone of Marine concrete - Yu Hu; Pan Chonggen; Shiyang Qu; Qunpeng Li; Sanqi Han (European Journal of Environmental and Civil Engineering, 2024)

Research progress of applications for nano-materials in improved QuEChERS method - Qi Zhou; Congcong Yu; Lingling Meng; Wenhua Ji; Songnan Liu; Canping Pan; Tao Lan; Lihong Wang; Bin Qu (Critical Reviews in Food Science and Nutrition, 2024)

Experimental investigation on the hydrodynamic performance of a bioinspired manta-ray underwater vehicle in various forward propulsion modes - Cheng Xing; Zhonghua Yin; Hanxuan Xu; Yonghui Cao; Yilin Qu; Qiaogao Huang; Guang Pan; Yong Cao (Ocean Engineering, 2024)

Assessment of microbial diversity in various saline soils driven by salt content - Dan Liu; Panpan Gao; Jiahe Niu; Zhaoqi Qu; Songnian Guo; Chenxiao Ding; Yanhong Lou; Quangang Yang; Hui Wang; Zhongchen Yang; Hongjie Di; Hong Pan; et al. (Pedobiologia, 2024)

3D Electrospun Nanofiber Sponges of Insect Chitosan/Pullulan/Citric Acid Embedded with ZnMOF in situ for Enhanced Healing of MRSA-Infected Wounds - Fuchen Jiang; Qing Li; Yingxi Li; Xiaomin Lai; Yun Duan; Arlene McDowell; Zhen Huang; Shuang Liu; Ying Wang; Chen Zhang; Yan Qu; Xiaoli Pan (Chemical Engineering Journal, 2024)

LAMAIS: A library-aided approach for efficient 1D 1H NMR qualitative analysis in plant metabolomics - Xinyuan Xie; Jiayu Yang; Yuting Lu; Yingting Shi; Jianyang Pan; Haibin Qu (Analytica Chimica Acta, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Revolutionizing food sustainability: Leveraging magnetic fields for food processing and preservation - Bai Qu; Guoqiang Shao; Na Yang; Kang Pan; Zhenlei Xiao; Yangchao Luo (Trends in Food Science & Technology, 2024)

Seismic performance of precast bridge bents with prestressed piles and new pocket connection design: Experimental and numerical study - Xinyan Jiang; Jianzhong Li; Pan Liu; Hongya Qu; Jianfeng Gao; Zehua Bao (Soil Dynamics and Earthquake Engineering, 2024)

Comprehensive analyses show the enhancement effect of exogenous melatonin on fluroxypyr-meptyl multiple phase metabolisms in Oryza sativa for reducing environmental risks - Zhao Jie Chen; Si Ying Li; Ya Nan Qu; Gan Ai; Yan Hui Wang; Dong Jin Pan; Hao Wen Wang; Dan Lu; Xiao Liang Liu (Pesticide Biochemistry and Physiology, 2024)

A novel process for efficient and selective recovery of potassium from phosphorus electrostatic precipitator dust using ionic liquids - Keheng Pan; Chi Zhao; Guangfei Qu; Yuqi Liang; Changfei Guo; Ping Ning (Journal of Cleaner Production, 2024)

Feasibility Study of Anisotropic Full-Waveform Inversion with DAS Data in a Vertical Seismic Profile Configuration at the Newell County Facility, Alberta, Canada - Luping Qu; Wenyong Pan; Kristopher Innanen; Marie Macquet; Donald Lawton (Surveys in Geophysics, 2024)

An improved time domain spectral matching method using particle swarm optimization - Pan Liu; Hongya Qu; Jianzhong Li; Gao Ma (Soil Dynamics and Earthquake Engineering, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Coupling cloud theory and concept hierarchy construction early warning thresholds for deformation safety of tailings dam - Shaohua Hu; Meixian Qu; Youcui Yuan; Zhenkai Pan (Natural Hazards, 2024)

Tracking investigation of archaeal composition and methanogenesis function from parental to offspring pigs - Qu Chen; Wentao Lyu; Chenglin Pan; Lingyan Ma; Yue Sun; Hua Yang; Wen Wang; Yingping Xiao (Science of The Total Environment, 2024)

Dual-color space color correction and histogram segmentation optimized strategy for underwater image enhancement - Dan Xiang; Dengyu He; Pan Gao; Huihua Wang; Chenkai Zhai; Qiang Qu; Chun Shan; Xing Zhu; Junliu Zhong (Earth Science Informatics, 2024)

Reconstructing the sound speed profile of South China Sea using remote sensing data and long short-term memory neural networks - Yu Zhao; Pan Xu; Guangming Li; Zhenyi Ou; Ke Qu (Frontiers in Marine Science, 2024)
Introduction Sound waves are refracted along the direction of their propagation owing to spatial and temporal fluctuations in the speed of sound in seawater. Errors are compounded when sound speed profiles (SSPs) with low precision are used to detect and locate distant underwater targets because an accurate SSP is critical for the identification of underwater objects based on acoustic data. Only sparse historical spatiotemporal data on the SSP of the South China Sea are available owing to political issues, its complex atmospheric system, and the unique topography of its seabed, because of which frequent oceanic movements at the mesoscale affect the accuracy of inversion of its SSP. Method In this study, we propose a method for the inversion of the SSP of the South China Sea based on a long short-term memory model. We use continuous-time data on the SSP of the South China Sea as well as satellite observations of the height and temperature of the sea surface to make use of the long-term and short-term memory-related capacities of the proposed model. Result It can achieve highly accurate results while using a small number of samples by virtue of the unique structure of its memory. Compared with the single empirical orthogonal function regression method, the inversion accuracy of this model is improved by 24.5%, and it performed exceptionally well in regions with frequent mesoscale movements. Discussion This enables it to effectively address the challenges posed by the sparse sample distribution and the frequent mesoscale movements of the South China Sea.

Tailoring raloxifene into single-component molecular crystals possessing multilevel stimuli-responsive room-temperature phosphorescence - Zhichao Pan; Jinming Song; Shasha Zhang; Ping Zeng; Ju Mei; Da-Hui Qu (Science Bulletin, 2024)

Uncertainty quantification of vibro-acoustic coupling problems for robotic manta ray models based on deep learning - Yilin Qu; Zhongbin Zhou; Leilei Chen; Haojie Lian; Xudong Li; Zhongming Hu; Yonghui Cao; Guang Pan (Ocean Engineering, 2024)

Investigating the influences of wind function parameterization on evaporation estimation using the generalized complementary principle - Xuxin Lei; Qu Li; Lei Cheng; Shujing Qin; Pan Liu; Lu Zhang (Journal of Hydrology, 2024)

Ultrasound-assisted fermentation for antioxidant peptides preparation from okara: Optimization, stability, and functional analyses - Mengxi Xie; Yuanyuan Ma; Feiyu An; Miao Yu; Lanwei Zhang; Xinyu Tao; Guoyang Pan; Qu Liu; Junrui Wu; Rina Wu (Food Chemistry, 2024)

In situ coupling metallophilic Zn sites and interfacial LiCl stabilizer to achieve one-step reversible hydrogen storage in Li/Na dual-cation borohydride - Shun Wang; Shanqing Qu; Zihua Liu; Yongyang Zhu; Zhenglong Li; Huifeng Liu; Mingxia Gao; Hongge Pan (Chemical Engineering Journal, 2024)

Self-assembly of GO-MXene hybrid composites by polyelectrolyte: As an efficient electrocatalyst for selective electrochemical detection of the antibiotic furazolidone - Kunling Wei; Keheng Pan; Guangfei Qu; Jin Qin; Jiaxin Lv; Yuqi Liang (Journal of Environmental Chemical Engineering, 2024)

Anisotropic materials based on carbohydrate polymers: A review of fabrication strategies, properties, and applications - Qi An; Jingnan Ren; Xiao Jia; Shasha Qu; Nawei Zhang; Xiao Li; Gang Fan; Siyi Pan; Zhifeng Zhang; Kangning Wu (Carbohydrate Polymers, 2024)

Effects of different ecological restoration methods on the soil bacterial community structure of a light rare earth tailings pond - Tianyu Chen; Ning Qu; Jinxiao Wang; Yaochen Liu; Jiao Feng; Shilei Zhang; Chunying Xu; Zhiquan Cao; Jun Pan; Chunlin Li (Plant and Soil, 2024)

Estimation of BDS-2/3 phase observable-specific signal bias aided by double-differenced model: an exploration of fast BDS-2/3 real-time PPP - Bao Shu; Yunqing Tian; Xuanyu Qu; Pan Li; Li Wang; Guanwen Huang; Yuan Du; Qin Zhang (GPS Solutions, 2024)
GNSS phase observable-specific signal bias (OSB) corrections are essential for widespread application of precise point positioning with ambiguity resolution (PPP-AR) or PPP-RTK. However, subject to the orbital error effects, conventional undifferenced (UD) model-derived BeiDou System (BDS) real-time (RT) OSB products are usually unsatisfactory. In this study, a novel OSB-generating method assisted by the double-differenced (DD) model is proposed. The reliable integer UD ambiguities are obtained by converting DD ambiguities with given ambiguity datums, by which the RT orbit error effects on ambiguity fixing can be reduced during the OSB extraction and PPP-AR process. Validated using data from two regional sparse GNSS reference networks in Shaanxi, China, and Europe, results show that the proposed method-derived OSB products can improve RT PPP-AR performance effectively. In the Shaanxi network, the narrow-lane ambiguity residuals for BDS-3 within ± 0.25 cycles are improved by 23.1% and 33.2% compared to those using the UD model and Centre National d’Etudes Spatiales (CNES)-derived OSB products, respectively, and the corresponding values are 15.2% and 43.1% in the European network. A centimeter- or even millimeter-level positioning accuracy can be achieved for BDS PPP using the poposed OSB products in both networks. In the kinematic PPP-AR test within the Shanxi network, the mean RMS of the BDS-2/3 fixed solutions in the east, north, and up directions is 0.9, 0.7, and 2.3 cm, with a decrease of 57.1%, 53.3%, and 46.5% compared to that using OSB derived by UD model. The median Time-To-First-Fix (TTFF) is also shortened from 23.8 to 7.5 min.

Identification of key factors affecting neonicotinoid residues in crops and risk of dietary exposure - Wenfei Yu; Ruxin Wu; Li Zhang; Yangzhong Pan; Jun Ling; Dan Yang; Jiajia Qu; Zhen Tao; Ruirui Meng; Yuexing Shen; Jingtong Yu; Nan Lin; et al. (Environmental Pollution, 2024)

Effects of different ecological restoration methods on the soil physicochemical properties and vegetation community characteristics of the Baotou light rare earth tailings pond in Inner Mongolia, China - Tianyu Chen; Ning Qu; Jinxiao Wang; Yaochen Liu; Jiao Feng; Shilei Zhang; Chunying Xu; Zhiquan Cao; Jun Pan; Chunlin Li (Environmental Science and Pollution Research, 2024)

A Rigid-Flexible Coupling Dynamic Model for Robotic Manta with Flexible Pectoral Fins - Yilin Qu; Xiao Xie; Shucheng Zhang; Cheng Xing; Yong Cao; Yonghui Cao; Guang Pan; Baowei Song (Journal of Marine Science and Engineering, 2024)
The manta ray, exemplifying an agile swimming mode identified as the median and paired fin (MPF) mode, inspired the development of underwater robots. Robotic manta typically comprises a central rigid body and flexible pectoral fins. Flexible fins provide excellent maneuverability. However, due to the complexity of material mechanics and hydrodynamics, its dynamics are rarely studied, which is crucial for the advanced control of robotic manta (such as trajectory tracking, obstacle avoidance, etc.). In this paper, we develop a multibody dynamic model for our novel manta robot by introducing a pseudo-rigid body (PRB) model to consider passive deformation in the spanwise direction of the pectoral fins while avoiding intricate modeling. In addressing the rigid-flexible coupling dynamics between flexible fins and the actuation mechanism, we employ a sequential coupling technique commonly used in fluid-structure interaction (FSI) problems. Numerical examples are provided to validate the MPF mode and demonstrate the effectiveness of the dynamic model. We show that our model performs well in the rigid-flexible coupling analysis of the manta robot. In addition to the straight-swimming scenario, we elucidate the viability of tailoring turning gaits through systematic variations in input parameters. Moreover, compared with finite element and CFD methods, the PRB method has high computational efficiency in rigid-flexible coupling problems. Its potential for real-time computation opens up possibilities for future model-based control.

Hydration mechanism of calcium chloride modiﬁed coal gasiﬁcation slag-based backﬁll materials - Geng Xie; Lang Liu; Yonglu Suo; Pan Yang; Caixin Zhang; Huisheng Qu; Yin Lv (Process Safety and Environmental Protection, 2024)

A new approach to extract the upright maize straw from Sentinel-2 satellite imagery using new straw indices - Jingping Zhou; Xiaohe Gu; Cuiling Liu; Wenbiao Wu; Yuchun Pan; Qian Sun; Sen Zhang; Xuzhou Qu (Computers and Electronics in Agriculture, 2024)

Positive effects of intercropping on soil phosphatase activity depend on the application scenario: A meta-analysis - Xinjing Qu; Yangwenke Liao; Chang Pan; Xiaogang Li (Soil and Tillage Research, 2024)

Insight into the comparison of key aroma-active compounds between camellia oils from different processing technology - Xiao Jia; Qi Zhou; Dou Huang; Nawei Zhang; Shasha Qu; Qi An; Qingshan Wang; Jingnan Ren; Hongyan Zhang; Siyi Pan; Gang Fan (Food Chemistry, 2024)

Monitoring maize lodging severity based on multi-temporal Sentinel-1 images using Time-weighted Dynamic time Warping - Xuzhou Qu; Jingping Zhou; Xiaohe Gu; Yancang Wang; Qian Sun; Yuchun Pan (Computers and Electronics in Agriculture, 2023)

Pore characteristics of sulfate-activated coal gasification slag cement paste backfill for mining - Geng Xie; Yonglu Suo; Lang Liu; Pan Yang; Huisheng Qu; Caixin Zhang (Environmental Science and Pollution Research, 2023)

Simultaneous electrochemical detection of dimethyl bisphenol A and bisphenol A using a novel Pt@SWCNTs-MXene-rGO modified screen-printed sensor - Guangfei Qu; Yun Zhang; Junhong Zhou; Huimin Tang; Wei Ji; Zhoupeng Yan; Keheng Pan; Ping Ning (Chemosphere, 2023)

Design and research of digital twin system for multi-environmental variable mapping in plant factory - Zihua Zhang; Zhenjiang Zhu; Guohua Gao; Daixuan Qu; Jinlei Zhong; Dongdong Jia; Xinyue Du; Xue Yang; Shiyue Pan (Computers and Electronics in Agriculture, 2023)

Synergistic assisted hydrogen production of tailings slurry and coal slurry: Process and mechanism investigation - Keheng Pan; Jijia Deng; Guangfei Qu; Kunling Wei; Yuqi Liang (Journal of Cleaner Production, 2023)

Hyperspectral estimation of maize (Zea mays L.) yield loss under lodging stress - Qian Sun; Xiaohe Gu; Liping Chen; Xuzhou Qu; Sen Zhang; Jingping Zhou; Yuchun Pan (Field Crops Research, 2023)

Reproducible Abnormalities and Diagnostic Generalizability of White Matter in Alzheimer’s Disease - Yida Qu; Pan Wang; Hongxiang Yao; Dawei Wang; Chengyuan Song; Hongwei Yang; Zengqiang Zhang; Pindong Chen; Xiaopeng Kang; Kai Du; Lingzhong Fan; Bo Zhou; et al. (Neuroscience Bulletin, 2023)

Research on energy loss characteristics during transient process of reactor coolant pump shaft stuck accident - Zehui Qu; Yibin Li; Yanlei Guo; Huan Zhou; Congxin Yang; Jun Pan; Xiuyong Wang (Annals of Nuclear Energy, 2023)

Late Carboniferous bimodal volcanic rocks of the West Junggar Terrane, NW China: Implications for the postcollisional tectonic setting of the southwestern CAOB - Xi Wang; Ran Wang; Pan Qu; Sanyou Cheng; Yonghui Xin (International Geology Review, 2023)

Diagnosis of soybean bacterial blight progress stage based on deep learning in the context of data-deficient - Xueying Wang; Tong Pan; Jinqiu Qu; Yongzhe Sun; Linxiao Miao; Ziming Zhao; Yang Li; Zhanguo Zhang; Hongjie Zhao; Zhenbang Hu; Dawei Xin; Qingshan Chen; et al. (Computers and Electronics in Agriculture, 2023)

New insight into copy number variations of goat SMAD2 gene and their associations with litter size and semen quality - Dwi Wijayanti; Yunyun Luo; Yangyang Bai; Chuanying Pan; Lei Qu; Zhengang Guo; Xianyong Lan (Theriogenology, 2023)

Organic fertilization integrated with water management to remediate As and Cd contamination in a paddy soil - Pan Sun; Chenchen Qu; Zhenqian Xiong; Yafeng Han; Fuhai Ma; Peng Cai; Wenli Chen; Qiaoyun Huang (Science of The Total Environment, 2023)

Silica nanoparticles induce pulmonary damage in rats via VEGFC/D–VEGFR3 signaling-mediated lymphangiogenesis and remodeling - Yanan Yu; Yujie Pan; Bing Chang; Xiaoxu Zhao; Kunlong Qu; Yuguo Song (Toxicology, 2023)

PM2.5 extended-range forecast based on MJO and S2S using LightGBM - Zhongqi Yu; Jinghui Ma; Yuanhao Qu; Liang Pan; Shiquan Wan (Science of The Total Environment, 2023)

Investigating the synergistic effects of magnesia-coal slag based solid waste cementitious materials and its basic characteristics as a backfill material - Pan Yang; Lang Liu; Yonglu Suo; Huisheng Qu; Geng Xie; Caixin Zhang; Shunchun Deng; Yin Lv (Science of The Total Environment, 2023)

Hexachloroplatinic(IV)-GO colloids as ideal electrodes modification materials for electrochemical sensing, HER and OER - Guangfei Qu; Junhong Zhou; Wei Ji; Huimin Tang; Kunling Wei; Yun Zhang; Keheng Pan; Ping Ning (Chemical Engineering Journal, 2023)

Analysis and simulation of nitrogen loss during water erosion process on windward slope under wind-driven rain conditions - Miaoying An; Weiming Xing; Yuguo Han; Jinxing Zhou; Zhixu Qu; Chenyang Zhao; Pan Xu (CATENA, 2023)

Experimental Investigation on the Effect of Strain Rate on Brittle Limestone in Post-earthquake Landslide Area - Shiqi Liu; Huanling Wang; Xiao Qu; Bing Pan; Wei-Chau Xie (Pure and Applied Geophysics, 2023)

Laboratory experiments on the evolution of a submerged berm driven by low-energy irregular waves - Y. Pan; X.K. Qu; Y.B. Yang; J.B. Zhang; G. Wang; S. Yin; Y.P. Chen (Coastal Engineering, 2023)

Nitrogen deposition further increases Ambrosia trifida root exudate invasiveness under global warming - Ke Xu; Xinyue Liu; Changxin Zhao; Qingmin Pan; Xiaoxing Chen; Ning Jiang; Cuiping Du; Yufeng Xu; Meini Shao; Bo Qu (Environmental Monitoring and Assessment, 2023)
Invasive plants can change the soil ecological environment in the invasion area to adapt to their growth and reproduction through root exudates. Root exudates are the most direct manifestation of plant responses to external environmental changes, but there is a lack of studies on root exudates of invasive plants in the context of inevitable global warming and nitrogen deposition. In this research, we used widely targeted metabolomics to investigate Ambrosia trifida root exudates during seedling and maturity under warming and nitrogen deposition to reveal the possible mechanisms of A. trifida adaptation to climate change. The results showed that the organic acids increased under warming condition but decreased after nitrogen addition in the seedling stage. Phenolic acids increased greatly after nitrogen addition in the mature stage. Most phenolic acids were annotated in the phenylpropane metabolic pathway and tyrosine metabolism. Therefore, nitrogen deposition may increase the adaptability of A. trifida through root exudates, making it more invasive under global warming. The results provide new ideas for preventing and controlling the invasion of A. trifida under climate change.

Weighted skip-connection feature fusion: A method for augmenting UAV oriented rice panicle image segmentation - Luolin Xiao; Zhibin Pan; Xiaoyong Du; Wei Chen; Wenpeng Qu; Youda Bai; Tian Xu (Computers and Electronics in Agriculture, 2023)

Provenances of the Oldest Xiashu loess and Xuancheng loess in southern China: Implications for dust transport and dust proxies of the East Asian winter monsoon - Chao Wu; Xiangmin Zheng; Peng Qian; Pan Qu; Miaohong He; Gangjian Wei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Basic characteristics of magnesium-coal slag solid waste backfill material: Part I. preliminary study on flow, mechanics, hydration and leaching characteristics - Pan Yang; Lang Liu; Yonglu Suo; Huisheng Qu; Geng Xie; Caixin Zhang; Shunchun Deng; Yin Lv (Journal of Environmental Management, 2023)

Process Monitoring and Characterization for Extraction of Herbal Medicines Based on Proton (1H) Nuclear Magnetic Resonance Spectroscopy and Multivariate Batch Modeling: a Case Study - Wenzhu Li; Fang Zhao; Jianyang Pan; Haibin Qu (Journal of Pharmaceutical Innovation, 2023)

Bifunctional Pt/Hβ catalyzed alkylation and hydrodeoxygenation of phenol and cyclohexanol in one-pot to synthesize high-density fuels - Zhensheng Shen; Gewei Zhang; Chengxiang Shi; Juncong Qu; Lun Pan; Zhenfeng Huang; Xiangwen Zhang; Ji-Jun Zou (Fuel, 2023)

Arsenic effects and behavior during the transformation of struvite to newberyite: Implications for applications of green fertilizers - Jinru Lin; Yidi Wang; Yuanming Pan; Shaofeng Wang; Xiaoming Zhao; Shan Qu; Zhenbing She; Kenan Cao; Zidan Yuan; Xu Ma; Reza Deevsalar; Yongfeng Jia (Chemical Engineering Journal, 2023)

Bioregulation of FeNi LDH morphology and electronic structure to highly promote electrocatalytic oxygen evolution - Guang Li; Chang Liu; Yun Yang; Xiuwen Pan; Tao Wu; Feng Zeng; Enyang Ma; Qing Qu; Lei Li (Chemical Engineering Journal, 2023)

Improveament of multiple attenuation and optimized impedance gradient for excellent multilayer microwave absorbers derived from two-dimensional metal–organic frameworks - Junjie Pan; Xinji Li; Wei Xia; Hongjiao Qu; Jingjing Li; Cheng Jiang; Tao Wang; Jianping He (Chemical Engineering Journal, 2023)

Amphiphilic chitosan/carboxymethyl gellan gum composite films enriched with mustard essential oil for mango preservation - Ziming Yang; Chen Guan; Chuang Zhou; Qingyan Pan; Zuyu He; Chao Wang; Yunhao Liu; Shuhui Song; Lijuan Yu; Yunhui Qu; Puwang Li (Carbohydrate Polymers, 2023)

Lipocalin-2-Mediated Insufficient Oligodendrocyte Progenitor Cell Remyelination for White Matter Injury After Subarachnoid Hemorrhage via SCL22A17 Receptor/Early Growth Response Protein 1 Signaling - Qiang Li; Xufang Ru; Yang Yang; Hengli Zhao; Jie Qu; Weixiang Chen; Pengyu Pan; Huaizhen Ruan; Chaojun Li; Yujie Chen; Hua Feng (Neuroscience Bulletin, 2022)
Insufficient remyelination due to impaired oligodendrocyte precursor cell (OPC) differentiation and maturation is strongly associated with irreversible white matter injury (WMI) and neurological deficits. We analyzed whole transcriptome expression to elucidate the potential role and underlying mechanism of action of lipocalin-2 (LCN2) in OPC differentiation and WMI and identified the receptor SCL22A17 and downstream transcription factor early growth response protein 1 (EGR1) as the key signals contributing to LCN2-mediated insufficient OPC remyelination. In LCN-knockdown and OPC EGR1 conditional-knockout mice, we discovered enhanced OPC differentiation in developing and injured white matter (WM); consistent with this, the specific inactivation of LCN2/SCl22A17/EGR1 signaling promoted remyelination and neurological recovery in both atypical, acute WMI due to subarachnoid hemorrhage and typical, chronic WMI due to multiple sclerosis. This potentially represents a novel strategy to enhance differentiation and remyelination in patients with white matter injury.

Mechanism exploration of brittle-plastic transformation of synthetic rocks in thermal environments - Huisheng Qu; Yonglu Suo; Lang Liu; Mengbo Zhu; Pan Yang; Caixing Zhang; Geng Xie (Bulletin of Engineering Geology and the Environment, 2022)

Niacin mitigates rumen epithelial damage in vivo by inhibiting rumen epithelial cell apoptosis on a high concentrate diet - Zhen Gao; Yanjiao Li; Chao Xu; Dan Luo; Qinghua Qiu; Ke Pan; Xiaowen Xiong; Mingren Qu; Kehui Ouyang (Veterinary Research Communications, 2022)

Sevoflurane inhibits the malignant phenotypes of glioma through regulating miR-146b-5p/NFIB axis - Haili Wang; Guofang Cheng; Lili Quan; Haibo Qu; Ailing Yang; Jiangge Ye; Yuanbo Feng; Xiaofang Li; Xiaoli Shi; Hua Pan (Metabolic Brain Disease, 2022)

Full-length MAVS, a mitochondrial antiviral-signaling protein, inhibits hepatitis E virus replication, requiring JAK-STAT signaling - Changbo Qu; Yang Li; Yunlong Li; Yihang Pan (Archives of Virology, 2022)
Hepatitis E virus (HEV) infection is the leading cause of acute hepatitis worldwide. The mitochondrial antiviral signaling protein (MAVS)-mediated interferon (IFN) response plays a pivotal role in hepatic antiviral immunity. However, little is known about the effect of overexpression of MAVS on HEV infection. Full-length MAVS (FL-MAVS) is the main form of MAVS that increases the production of IFNs. Here, we studied the effect of FL-MAVS on HEV infection. We found that overexpression of FL-MAVS profoundly inhibited HEV replication. Furthermore, we showed that the anti-HEV effect of FL-MAVS is largely dependent on JAK-STAT signaling activation.

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

A new Fe-C porous filter material from dredged sediment: preparation, characterization, and its application - Shuyi Chu; Qian Qu; Keke Pan; Yunjie Xu; Jibo Xiao (Environmental Science and Pollution Research, 2021)

Insertion/deletion variants within the IGF2BP2 gene identified in reported genome-wide selective sweep analysis reveal a correlation with goat litter size - Dongyun Xin; Yangyang Bai; Yi Bi; Libang He; Yuxin Kang; Chuanying Pan; Haijing Zhu; Hong Chen; Lei Qu; Xianyong Lan (Journal of Zhejiang University-SCIENCE B, 2021)

Research on Meso-mechanism of Failure Mode of Tunnel in Jointed Rock Mass - Tong Qu; Zhongchang Wang; Wenting Zhao; Ke Pan (Geotechnical and Geological Engineering, 2021)

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Propofol Protects Regulatory T Cells, Suppresses Neurotoxic Astrogliosis, and Potentiates Neurological Recovery After Ischemic Stroke - Yuzhu Wang; Dan Tian; Yushang Zhao; Mengyao Qu; Yuhualei Pan; Changwei Wei; Yanbing Zhu; Anshi Wu (Neuroscience Bulletin, 2021)

Characterization of Lactobacillus reuteri WQ-Y1 with the ciprofloxacin degradation ability - Chunxiao Qu; Zhen Wu; Daodong Pan; Zhendong Cai; Xiaotao Liu (Biotechnology Letters, 2021)

Gastronautidae Deroux, 1994 and Trithigmostoma Jankowski, 1967: Evolutionary Links Among Cyrtophorian Ciliates (Protista, Ciliophora, and Phyllopharyngea) - Zhishuai Qu; Hongbo Pan; Congcong Wang; Honggang Ma; Thorsten Stoeck; Xiaozhong Hu (Frontiers in Marine Science, 2021)
Studies on cyrtophorian ciliates (Cyrtophoria) have accumulated much knowledge on morphological taxonomy and molecular phylogeny, and the general classification and phylogenetic relationships of most families have thereby been revealed. However, the phylogenetic position of the family Gastronautidae Deroux, 1994 remains uncertain. This is due to the presence of specialized characteristics (in particular a circumoral kinety in a closed circle), and most importantly, the lack of molecular data of this family. In addition, Trithigmostoma Jankowski, 1967 holds a special position among genera in Chilodonellidae Deroux, 1976 due to its divergent characteristics. In the present work, we studied a new gastronautid, Gastronauta paraloisi sp. n., and three populations of Trithigmostoma cucullulus ( Müller, 1786 ) Jankowski, 1967 , using integrative methods. Species identifications were confirmed by morphological research. We also obtained SSU rDNA sequences, which included the first available sequence of Gastronautidae. The following SSU rDNA-inferred phylogenetic analyses showed that the establishment of the family Gastronautidae is necessary, and Gastronautidae and Trithigmostoma may represent intermediate evolutionary links in the order Chlamydodontida.

Upregulation of endothelial cell-derived exosomal microRNA-125b-5p protects from sepsis-induced acute lung injury by inhibiting topoisomerase II alpha - Lijing Jiang; Jindi Ni; Guofeng Shen; Zhuye Xia; Lu Zhang; Shihong Xia; Shengfu Pan; Hongping Qu; Xiang Li (Inflammation Research, 2021)

Fetal growth, fetal development, and placental features in women with polycystic ovary syndrome: analysis based on fetal and placental magnetic resonance imaging - Qing Zhang; Zhong-kun Bao; Mei-xiang Deng; Qiong Xu; Dan-dan Ding; Man-man Pan; Xi Xi; Fang-fang Wang; Yu Zou; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2020)

CRISPR/Cas9 genome editing shows the important role of AZC_2928 gene in nitrogen-fixing bacteria of plants - Xiaojing Wang; Sang Lv; Tao Liu; Jiale Wei; Shiyuan Qu; Yi Lu; Junbiao Zhang; Sanda Oo; Baohong Zhang; Xiaoping Pan; Huawei Liu (Functional & Integrative Genomics, 2020)

MiR-155 inhibition alleviates suppression of osteoblastic differentiation by high glucose and free fatty acids in human bone marrow stromal cells by upregulating SIRT1 - Bo Qu; Jun He; Zhimou Zeng; Hongsheng Yang; Zhanli Liu; Zongrui Cao; Hua Yu; Wen Zhao; Xianming Pan (Pflügers Archiv - European Journal of Physiology, 2020)

Diversity Distributions and the Anthocyanin Associations of Fungal Endophytes in Different Colored Grapevine Leaves - Jing-Chao Chen; Man Yu; Fang Liu; Jin-Zhuo Qu; Xiao-Xia Pan; Han-Bo Zhang; Ming-Zhi Yang (Journal of Plant Biology, 2020)

The Role of Cross-Pathway Control Regulator CpcA in the Growth and Extracellular Enzyme Production of Penicillium oxalicum - Yunjun Pan; Liwei Gao; Xiujun Zhang; Yuqi Qin; Guodong Liu; Yinbo Qu (Current Microbiology, 2020)

Microsatellite records for volume 11, issue 3 - Pengfei Hu; Hao-Xiang Liu; Ying Pan; Yan-Fu Qu; Xueqi Tian; Ke-Xin Wang; Yu-Heng Wei; Xue-Ping Wu; Xiumei Xing; Zhengyi Zhang; Pei Zhao; Yu-Tian Zhao; et al. (Conservation Genetics Resources, 2019)

Monthly variations of fucoidan content and its composition in the farmed brown alga Saccharina sculpera (Laminariales, Phaeophyceae) - Yanyan Qu; Zengmei Cao; Weiwei Wang; Na Wang; Xiaojie Li; Jinhua Pan (Journal of Applied Phycology, 2019)

Prediction on landslide displacement using a new combination model: a case study of Qinglong landslide in China - Weidong Wang; Jiaying Li; Xia Qu; Zheng Han; Pan Liu (Natural Hazards, 2019)

Lactobacillus futsaii subsp. chongqingii subsp. nov., Isolated from a Traditional Chinese Pickle - Xin Du; Kang Cao; Mingzheng Tan; Qu Pan (Current Microbiology, 2019)

Ecological Effects of Single-Walled Carbon Nanotubes on Soil Microbial Communities and Soil Fertility - Haifeng Qian; Mingjing Ke; Qian Qu; Xingxing Li; Benben Du; Tao Lu; Liwei Sun; Xiangliang Pan (Bulletin of Environmental Contamination and Toxicology, 2018)

Effects of Soil Residual Plastic Film on Soil Microbial Community Structure and Fertility - Haifeng Qian; Meng Zhang; Guangfu Liu; Tao Lu; Qian Qu; Benben Du; Xiangliang Pan (Water, Air, & Soil Pollution, 2018)

Modification of PPTA-based polymeric waste and adsorption properties for metal ions - J. J. Gao; R. J. Qu; S. S. Li; F. W. Pan; X. H. Jia; C. M. Sun; Y. Zhang; Q. L. Ma; C. X. Li (International Journal of Environmental Science and Technology, 2018)

Diversity of the cyrtophorid genus Chlamydodon (Protista, Ciliophora): its systematics and geographic distribution, with taxonomic descriptions of three species - Zhishuai Qu; Lifang Li; Xiaofeng Lin; Thorsten Stoeck; Hongbo Pan; Khaled A. S. Al-Rasheid; Weibo Song (Systematics and Biodiversity, 2018)

Effects of body mass index on the outcomes of in vitro fertilization in Chinese patients with polycystic ovary syndrome: a retrospective cohort study - Xiao-ming Pan; Zhong Lin; Nan Li; Jia-qi Wu; Dan-qing Chen; Yi-min Zhu; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2018)

Nutrients Other than Selenium Are Important for Promoting Children’s Health in Kashin-Beck Disease Areas - Yujie Ning; Xi Wang; Xiong Guo; Pan Zhang; Pengfei Qu; Feng Zhang; Sen Wang; Yanxia Lei; Mikko Lammi (Biological Trace Element Research, 2018)

Comparative Transcriptome Analysis of Rhizoctonia solani-resistant and -Susceptible Rice Cultivars Reveals the Importance of Pathogen Recognition and Active Immune Responses in Host Resistance - Zhengjie Yuan; Yu Zhang; Guojuan Xu; Dongling Bi; Haiyan Qu; Xiaowei Zou; Xiaoqing Gao; Haihe Yang; Haiyan He; Xuli Wang; Jiandong Bao; Shimin Zuo; et al. (Journal of Plant Biology, 2018)

American, European, and Chinese practice guidelines or consensuses of polycystic ovary syndrome: a comparative analysis - Fang-fang Wang; Jie-xue Pan; Yan Wu; Yu-hang Zhu; Paul J. Hardiman; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2018)

AMPK/NF-κB signaling pathway regulated by ghrelin participates in the regulation of HUVEC and THP1 Inflammation - Min Zhang; Shuping Wang; Zhicheng Pan; Tiantong Ou; Jianwei Ma; Hua Liu; Ruogu Li; Ping Yang; Wenzheng Han; Shaofeng Guan; Xumin Hou; Weiyi Fang; et al. (Molecular and Cellular Biochemistry, 2018)

Nucleoside analogue 2’-C-methylcytidine inhibits hepatitis E virus replication but antagonizes ribavirin - Changbo Qu; Lei Xu; Yuebang Yin; Maikel P. Peppelenbosch; Qiuwei Pan; Wenshi Wang (Archives of Virology, 2017)

QTL mapping of domestication and diversifying selection related traits in round-fruited semi-wild Xishuangbanna cucumber (Cucumis sativus L. var. xishuangbannanesis) - Yupeng Pan; Shuping Qu; Kailiang Bo; Meiling Gao; Kristin R. Haider; Yiqun Weng (Theoretical and Applied Genetics, 2017)

Metagenomic analysis reveals the influences of milk containing antibiotics on the rumen microbes of calves - Wei Li; Yunsheng Han; Xue Yuan; Guan Wang; Zhibo Wang; Qiqi Pan; Yan Gao; Yongli Qu (Archives of Microbiology, 2017)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

The transcription factor TBX2 regulates melanogenesis in melanocytes by repressing Oca2 - Yu Chen; Li Pan; Zhongyuan Su; Jing Wang; Huirong Li; Xiaoyin Ma; Yin Liu; Fan Lu; Jia Qu; Ling Hou (Molecular and Cellular Biochemistry, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Knockdown of NOB1 expression inhibits the malignant transformation of human prostate cancer cells - Xiangmin Zhang; Dongxu Zhang; Fajun Qu; Yi Hong; Jianwei Cao; Xiuwu Pan; Lin Li; Yi Huang; Hai Huang; Lei Yin; Lu Chen; Jizhong Ren; et al. (Molecular and Cellular Biochemistry, 2014)

Matrix Metalloproteinase-14 Expression and Its Prognostic Value in Cervical Carcinoma - Huayi Wang; Xianhua Zhang; Liming Huang; Jia Li; Shuyun Qu; Fenglian Pan (Cell Biochemistry and Biophysics, 2014)

Tonoplast Lipid Composition and Proton Pump of Pineapple Fruit During Low-Temperature Storage and Blackheart Development - Yuchan Zhou; Xiaoping Pan; Hongxia Qu; Steven J. R. Underhill (The Journal of Membrane Biology, 2014)

Stress fermentation strategies for the production of hyperthermostable superoxide dismutase from Thermus thermophilus HB27: effects of ions - Hu Zhu; Jianguo Liu; Jianbo Qu; Xinliang Gao; Tao Pan; Zhanfeng Cui; Xiubo Zhao; Jian R. Lu (Extremophiles, 2013)

Antifungal Metabolites Produced by Chaetomium globosum No.04, an Endophytic Fungus Isolated from Ginkgo biloba - Guizhen Zhang; Yanhua Zhang; Jianchun Qin; Xiaoyan Qu; Jinliang Liu; Xiang Li; Hongyu Pan (Indian Journal of Microbiology, 2013)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

Functional Identification of a Putative β-Galactosidase Gene in the Special lac Gene Cluster of Lactobacillus acidophilus - Qu Pan; Junmin Zhu; Lina Liu; Yanguang Cong; Fuquan Hu; Jinchuan Li; Xiaoping Yu (Current Microbiology, 2010)

Inducible expression of human angiostatin by AOXI promoter in P. pastoris using high-density cell culture - Ai-Lian Zhang; Tian-Yuan Zhang; Jin-Xian Luo; Ce-Yi Fu; Zhi Qu; Guo-Hui Yi; Dong-Xiao Su; Fa-Zhi Tu; Ying-Wen Pan (Molecular Biology Reports, 2009)

FLIM and emission spectral analysis of caspase-3 activation inside single living cell during anticancer drug-induced cell death - Wenliang Pan; Junle Qu; Tongsheng Chen; Lei Sun; Jing Qi (European Biophysics Journal, 2009)

Identification and Experimental Verification of Protective Antigens Against Streptococcus suis Serotype 2 Based on Genome Sequence Analysis - Lina Liu; Gong Cheng; Changjun Wang; Xiuzhen Pan; Yanguang Cong; Qu Pan; Jing Wang; Feng Zheng; Fuquan Hu; Jiaqi Tang (Current Microbiology, 2009)

Cloning and Characterization of a Novel, Human Cellular Retinaldehyde-binding Protein CRALBP-like (CRALBPL) Gene - Ya-Hui Kong; Guang-Ming Ye; Kai Qu; Wen-Qi Pan; Xiang-Hua Liu; Bo Wan; Jin-Hu Guo; Long Yu (Biotechnology Letters, 2006)

Airway hyperresponsiveness induced by repetitive intraperitoneal injection of lipopolysacharide and the involvement of inflammation and nitric oxide in guinea pigs - H. Jiang; J. Qu; L. He; J. Pan; X. Chen; L. Li; D. Zhu; Y. Cao (Inflammation Research, 2006)

Projections of diencephalic dopamine neurons into the spinal cord in mice - S. Qu; W. G. Ondo; X. Zhang; W. J. Xie; T. H. Pan; W. D. Le (Experimental Brain Research, 2006)